Effectiveness Evaluation of "Refining Instruction and Support for Staff in Medical Education" Program on Improving the Knowledge Perspectives of Medical Education Development Office Experts - Parvin Rezaei Gazki; Somayeh Noori Hekmat; Mahla Salajegheh (Journal of Medical Education and Development)
Introduction: The importance of human resources in medical universities has received special attention. Given the vital role of education development office experts in improving the education in medical universities, this study aimed to evaluate the effectiveness of the training program "Refining Instruction and Support for staff in Medical Education" on improving the knowledge and perspectives of medical education development office experts. Method: A quasi-experimental study was designed to implement and evaluate a medium-term program which was developed based on literature review, study of upstream documents, and needs assessment through focus groups with medical education experts. The program consisted of eight training workshops. Which was conducted as a census on 16 experts from the development offices of Kerman University of Medical Sciences. Effectiveness was evaluated through pre-test and post-test. Results: A significant increase in the knowledge of the participants was observed, so that the average scores increased from 2.05 ± 1.87 to 3.75 ± 1.51, with the greatest change observed in the area of ​​guiding gifted students. Also, in this study, the experts' perspective score increased from 73.11 ± 12.83 to 76.83 ± 7.88, indicating a positive change in their perspective towards their role in improving education. Conclusion: These findings emphasize the necessity of specialized training for experts from education development offices and indicate that such programs can strengthen the culture of continuous learning and professional development.